Effect of Selective Serotonin Reuptake Inhibitors on Coagulation: Fact or Fiction? - Antoine Mokhtarian; Sophie Melicine; Virginie Siguret; Georges Jourdi (Clinical and Translational Science)
ABSTRACT Selective serotonin reuptake inhibitors (SSRIs) are commonly prescribed for depression and anxiety yet are associated with an increased bleeding risk. While this risk is mainly linked to the decrease in platelet serotonin content, thus abnormal platelet functions, some studies suggest an inherent effect of SSRIs on coagulation. Hence, we performed a literature review to provide an overview of the different studies assessing SSRI's effects on coagulation assays routinely used in clinical practice. A search of the PubMed database yielded 22 relevant studies. Results were inconsistent: While some studies showed minor changes in routine coagulation assays, namely, prothrombin time and activated partial thromboplastin time, the majority found no significant effects of SSRIs on coagulation tests. Then, we specifically investigated the impact of citalopram, a commonly prescribed SSRI, on the thrombin generation assay (TGA) allowing the detection of any potential procoagulant or anticoagulant effect. TGA was performed in platelet‐poor plasma from 14 healthy volunteers spiked with citalopram at therapeutic (0.1 and 0.5 μM) and supratherapeutic (50 μM) concentrations. TGA parameters were not significantly changed compared to the control condition regardless of the citalopram concentration. All in all, our findings failed to demonstrate any compromised coagulation function associated with SSRI therapy.